EFFECT OF MUSHROOM RESIDUES, DATE RESIDUES AND BACTERIAL INOCULUM ON RHIZOSPHERIC SOIL PROPERTIES OF BROCCOLI PLANT - J. A. Al-Obidiy; H. J. Mohammed; J. S. Alkobaisy (مجلة الأنبار للعلوم الزراعية, 2025)
A field experiment was conducted in one of College of Agriculture fields, University of Anbar, Ramadi, Iraq, for autumn 2022-2023 to study the effect of each white fungus residue, date residues, and biofertilizer on some soil properties. The experiment included three factors: white mushroom residues at three levels of 0, 10, and 20 tons ha-1, which was symbolized by (M0, M1, M2), and date waste in three levels of 0, 10, and 20 tons ha-1. It was symbolized by (D0, D1, D2) and the bacterial inoculum consisting of (Azotobacter chroococcum+Pseudomonas putida) in two levels without adding and symbolizing, and it was symbolized (B0) and adding the inoculate and symbolizing it with (B1). A factorial experiment with three replications was designed with a randomized complete block design (RCBD). Broccoli seedlings were planted on 10/7/2022 after conducting land and crop service operations. The crop was harvested on 3/3/2023, and soil samples were analyzed before and after planting. The results of the statistical analysis showed that the triple interference with the highest levels (M2D2B1) showed a significant increase in the content of organic matter, microbial density, and concentrations of nitrogen, phosphorus, and potassium available in the soil, which recorded 12.15 g kg -1 and 3.81710×cfu gm-1  soil and 154.40, 18.07, 287.54 mg kg-1, the single treatments of white fungus residue, date residue, and bacterial inoculum recorded a significant decrease in each of the bulk density and saturated water conductivity, and a significant increase in the total porosity of the soil, which recorded bulk density rates of 1.30, 1.30 and 1.25 Mg.m-3, respectively. The saturated water conductivity rates were 2.48, 2.55, and 2.56 cm h-1, respectively, and the total porosity rates were 51.32, 51.26, and 51.12%, respectively. The comparison treatment without additions (M0D0B0) showed the lowest rates for all the studied soil characteristics, namely organic matter content, microbial density, concentrations of nitrogen, phosphorus, and potassium available in the soil, bulk density, saturated water conductivity, and total soil porosity, as it recorded 2.10 g kg -1, 0.54 710×cfu. gm-1 soil, 32.13 mg kg-1, 9.55 mg kg-1, 206.55 mg kg-1, 1.35 Mg. m-3, 2.75 cm h-1, 47.26%, respectively